Progressive migration of slab break-off along the southern Tyrrhenian plate boundary: Constraints for the present day kinematics. (April 2017) - Chiarabba, Claudio; Palano, Mimmo
Graphical abstract: Abstract: The Ionian subduction in the central Mediterranean, just 200 km wide, is one of the narrowest in the world. Its evolution has involved a progressive disruption of the subducting slab, contemporaneous to the retreat and step-wise opening of back-arc basins. In this study, we analyse velocity anomalies of the upper mantle, together with the most comprehensive set of earthquake locations and kinematic indicators available for Italy, to reconstruct the geodynamics and tectonic evolution of the Ionian subduction system. Along the Sicilian boundary, we identify an eastward migration of the slab edge with detachment of the Ionian oceanic lithosphere. We hypothesize that the progressive detachment of the slab took place along lithospheric transform faults of the Neo-Tethys Ocean. Among the main active kinematic elements of the Ionian accretionary wedge, we suggest that a ∼400-km-long and highly segmented shear zone formed by the Aeolian-Tindari-Letojanni fault system and the Ionian fault represents the surface expression of such a lithospheric tearing. The present day convergence between the Eurasian and African plates is accommodated both at the frontal thrust of the flexed Hyblean margin in southern Sicily and offshore along the Tyrrhenian Sea. Lithospheric bending favors the wedging of the mantle underneath northern Sicily, while magmatic fluids are channeled along slab tears.